2014
DOI: 10.4162/nrp.2014.8.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Women Infant and Children program participants' beliefs and consumption of soy milk : Application of the Theory of Planned Behavior

Abstract: The purpose of this study was to determine if Theory of Planned Behavior (TPB) variables predict soy milk intake in a sample of WIC participants in 2 Illinois counties (n = 380). A cross-sectional survey was used, which examined soy foods intake, behavioral beliefs, subjective norms, motivation, and intention. Soy product intake was low at both sites, and many participants (40%) did not know that soy milk was WIC approved. Most (> 70%) wanted to comply with their health care providers, but didn't know their op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…According to the findings of this study, subjective norms did not have a positive and significant influence on the intention to purchase plant-based yogurt alternative products. This finding was inconsistent with several previous studies [ 27 , 43 , 45 , 60 ].…”
Section: Discussioncontrasting
confidence: 99%
“…According to the findings of this study, subjective norms did not have a positive and significant influence on the intention to purchase plant-based yogurt alternative products. This finding was inconsistent with several previous studies [ 27 , 43 , 45 , 60 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our results show that compared with non-consumers, soy milk consumers had higher cognitive functioning, including both global and verbal memory scores. Previous studies suggested the beneficial role of soy consumption to health, for example, the link has been found between increased soy consumption and lower risk of incidence and prognosis of osteoporosis, coronary heart diseases ( 41 ), breast cancer ( 42 ), and diabetes ( 43 ). However, studies exploring the benefit of consuming soy products in cognitive functioning were inconsistent ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…During a 6‐month intervention period conducted from January 2016 to September 2017, an RD blogger published one new blog post each week in which positive, nonrestrictive messages integrated theory‐based intervention methods (e.g., modelling, goal setting, and provision of feedback on performance) selected from evidence‐based taxonomies (Kok et al, ; S. Michie et al, ). Theory‐based intervention methods were selected on the basis of their effectiveness to promote changes in the theoretical constructs predicting the consumption of vegetables and fruit and milk and alternatives in adults (i.e., knowledge, beliefs about consequences [e.g., perceptions of advantages/disadvantages], beliefs about capabilities [e.g., perceptions of barriers/facilitators], and intention and goals; Brewer, Blake, Rankin, & Douglass, ; Guillaumie, Godin, & Vezina‐Im, ; Kim, Reicks, & Sjoberg, ; Park & Ureda, ; Wheeler & Chapman‐Novakofski, ) and in light of their feasibility of delivery using a blog, as described elsewhere (Dumas et al, ). Blog messages also aimed to promote healthy food changes in the home environment and encourage involvement of children in family meal planning and preparation, which, in turn, aimed to improve the quality of children's diet.…”
Section: Methodsmentioning
confidence: 99%